Cooperative experiences among small rural producers in Tangará da Serra – MT - Alves de Lima, Aparecida de Fátima (REBRAE, 2016)
Collective organizations represent an important option to small rural producers face together the difficulties caused by a context of turbulence and intense competition. Despite of its relevance, studies have shown that cooperative organizations have weaknesses in regards to balance the different levels of interest from the partners: the economic, social and political about the practices and management strategies adopted. In this context, the problem arises: To what extent the specific features of cooperative organizations influence in their competitiveness and which are the factors to be considered in the strategic management of these organizations to be competitive while remaining cooperative. This work focuses in cooperative organization of small rural producers in the context of rural settlements in order to analyzing the influences of the organizational environment, the social participation in decisions and the economic and social efficiency of these organizations. It was used a descriptive, qualitative and quantitative methodological approach. Due to be an understudied subject in the State of Mato Grosso was classified as exploratory and supported by a literature review which refers to Cooperatives, Economics, Management and Sociology. The field work demanded structures questionnaires and semi-structured interview routines, informal conversations and non-participant observation in meetings of these organizations. It was found that partners who are preparing to assume management positions in cooperative organizations bring experiences and values accumulated during their existence and these attributes not always are compatible with the principles of cooperation. For analyzed cooperatives achieve economic, social, organizational and administrative advantages it is necessary to overcome the limitations, mainly in organizational, managerial and cooperative education dimensions.